Sleep‐disordered breathing was associated with lower health‐related quality of life and cognitive function in a cross‐sectional study of older adults. Issue 9 (17th May 2022) - Ward, Stephanie A.; Storey, Elsdon; Gasevic, Danijela; Naughton, Matthew T.; Hamilton, Garun S.; Trevaks, Ruth E.; Wolfe, Rory; O'Donoghue, Fergal J.; Stocks, Nigel; Abhayaratna, Walter P.; Fitzgerald, Sharyn; Orchard, Suzanne G.; et al.
Abstract: Background and objective: The clinical significance of sleep‐disordered breathing (SDB) in older age is uncertain. This study determined the prevalence and associations of SDB with mood, daytime sleepiness, quality of life (QOL) and cognition in a relatively healthy older Australian cohort. Methods: A cross‐sectional analysis was conducted from the Study of Neurocognitive Outcomes, Radiological and retinal Effects of Aspirin in Sleep Apnoea. Participants completed an unattended limited channel sleep study to measure the oxygen desaturation index (ODI) to define mild (ODI 5–15) and moderate/severe (ODI ≥ 15) SDB, the Centre for Epidemiological Studies Scale, the Epworth Sleepiness Scale, the 12‐item Short‐Form for QOL and neuropsychological tests. Results: Of the 1399 participants (mean age 74.0 years), 36% (273 of 753) of men and 25% (164 of 646) of women had moderate/severe SDB. SDB was associated with lower physical health‐related QOL (mild SDB: beta coefficient [ β ] −2.5, 95% CI −3.6 to −1.3, p  < 0.001; moderate/severe SDB: β −1.8, 95% CI −3.0 to −0.6, p  = 0.005) and with lower global composite cognition (mild SDB: β −0.1, 95% CI −0.2 to 0.0, p  = 0.022; moderate/severe SDB: β −0.1, 95% CI −0.2 to 0.0, p  = 0.032) compared to no SDB. SDB was not associated with daytime sleepiness nor depression. Conclusion: SDB was associated with lower physical health‐related quality of life and cognitive function. Given the high prevalence of SDB in older age, assessing QOL and cognition may better delineate subgroups requiring further management, and provide useful treatment target measures for this age group. Abstract : The clinical implications for sleep‐disordered breathing (SDB) in older age remain uncertain. This study of healthy community‐dwelling older Australians reports significant associations between SDB and a lower physical health‐related quality of life, in contrast to other studies of SDB in older age, and between SDB and lower cognitive function. See related editorial